A qualitative study on how older adults perceive the meaning and shaping of optimism: has the COVID-19 pandemic impacted their perceptions? - Heather Craig; Danijela Gasevic; Joanne Ryan; Rosanne Freak-Poli; Stella Talic (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Optimism is a psychosocial asset associated with healthy ageing. Coronavirus disease 2019 (COVID-19) tremendously impacts people's lives and health. This study explored what optimism means to older Australians and how the pandemic may have affected their perceptions. # Methods Eleven adults (55% female), aged 68-74 years, living in metropolitan and regional areas of Australia participated in semi-structured interviews via video-conferencing. Participants' perceptions of optimism, lived experience, and potential impacts of the pandemic on optimism were explored. Data were evaluated using reflective thematic analysis. # Findings The themes identified were: (i) the essence, beliefs and meaning of optimism, (ii) personality and disposition in shaping optimism through the life course, and (iii) the effects and aftermath of a stressor. Genetics and family history, gratitude and hopefulness, life-course development and the life journey shaped optimism. Pragmatic beliefs and attitudes, being solution-focused, and positivity contributed to the lifelong development of optimism. Optimism promoted proactive coping strategies and acceptance of difficulties during the pandemic. # Conclusions The overall meaning of optimism was a generalised positive outlook shaped by the dynamic interaction of attributes. Optimism was not impacted by the pandemic stressor. Rather, optimism helped individuals handle this stressful time. Optimism may aid older individuals' recovery from the effects of COVID-19.